GENDER EQUALITY AND FAITH-BASED REGULATION - Rosana, Yenni (JURNAL LITERARY CRITICISM, 2015)
This paper discusses women?s struggle in achieving the rights to be equal by comparing between Australia and Indonesia. This paper is a literature review that aims to analyze the differences and similarities faced by feminist in the two countries that adopt very different socio-cultural background, Western culture in Australia and Eastern culture in Indonesia. Besides, Islam as the religion of majority Indonesians is often blamed to barrier women to have equal right. Meanwhile, in Australia, being engaged in a religion is not compulsory and Muslims are the minority. Interestingly, there are contradict arguments, while many argued the influence of Western to support women in Indonesia to receive their rights; the history has recorded that Muslim women in Indonesia had attained higher education equal to men and had important positions in politics long before the term women emancipation was introduced in Australia. The methodology of writing is by analyzing secondary data from published literature on the issue. Moreover, this study found out that the ideological backgrounds of majority populations in each country influence gender equality achievement. From the two themes discussed (1) The Voice of the Majority in Determining the Implemented Law, (2) Faith-Based Organization and Woman Emancipation. The conclusion here,  there are controversial regulations in Islam including burqa banning and polygamy, however, how those regulations stated in Muslims? scripture are often misinterpreted. The rule of civil society organizations is important to empower women however beyond that is to understand the voice of majority populations to succeed in the program implementation. Keywords: women equality, gender, faith, Muslim, Islam, Indonesia, Australia,